Pela Gandong from the Perspective of Christian Religious Education - Frets Keriapy; Talizaro Tafonao (Sekolah Tinggi Theologia Nazarene Indonesia, 2023)
Local wisdom that develops in every region in Indonesia is an important thing that must be developed and planted in every layer of society. One of the local pearls of wisdom developed in Maluku is Pela Gandong. Pela Gandong has long been developed in Maluku, but unfortunately, it has not been rooted and has become flesh and blood of every person in Maluku. The conflict that occurred in 1999-2000 is the evidence. Thus, this research aims to make Maluku's local wisdom Pela Gandong necessary for living in harmony in post-conflict times. Using qualitative research literature-based, the authors found that even though the root of the conflict was not in religion but in politics and the economy, the flourishing of local wisdom Pela Gandong could fortify any threats from outside. Therefore, this is where the role of Christian Education is to instil the attitude of Pela Gandong in every student. The task of flourishing Pela Gandong is not only the responsibility of the family and society, but education is an important means of enriching it.